Exercise and Cardiovascular Diseases - Massimo Villella; Alessandro Villella (Karger Publishers, 2014)
Exercise is a physiologic stressor that has multiple beneficial effects on cardiovascular system. Currently exercise training is a class I intervention as part of a multifactorial long-term process that includes: clinical assistance, assessment of global cardiovascular risk, identification of specific objective for each cardiovascular risk factor, formulation of an individual treatment plan with multiple intervention aimed at reduction of the risk, educational programs, planning of long term follow-up. This paper reviews the evidences of benefit of exercise in the most common heart diseases and describes the role of exercise training in the cardiac rehabilitation programs.